Systematic review of p38 mitogen-activated kinase and its functional role in reproductive tissues - Sheller-Miller, Samantha; Richardson, Lauren; Martin, Laura [UNESP]; Jin, Jin; Menon, Ramkumar (Wiley, 2018)
Oxidative stress (OS) plays a role in uterine tissue remodeling during pregnancy and parturition. While p38 MAPK is an OS-response kinase, a precise functional role is unknown. Therefore, we conducted a systematic review of literature on p38 MAPK expression, activation, and function in reproductive tissues throughout pregnancy and parturition, published between January 1980 and August 2017, using four electronic databases (Web of Science, PubMed, Medline, and CoCHRANE). We identified 418 reports; 108 were selected for full-text evaluation and 74 were included in final review. p38 MAPK was investigated using feto-maternal primary or immortalized cells, tissue explants, and animal models. Western blot was most commonly used to report phosphorylated (active) p38 MAPK. Human placenta (27), chorioamniotic membranes (14), myometrium (13), decidua (8), and cervix (1) were the studied tissues. p38 MAPK's functions were tissue and gestational age dependent. Isoform specificity was hardly reported. p38 MAPK activity was induced by ROS or proinflammatory cytokines to promote cell signaling linked to cell fate, primed uterus, ripened cervix, and proinflammatory cytokine/chemokine production. In 35 years, reports on p38 MAPK's role during pregnancy and parturition are scarce and current literature is insufficient to provide a comprehensive description of p38 MAPK's mechanistic role during pregnancy and parturition.
Keywords: amniochorion; cervix; decidua; MAPK signaling; myometrium; placenta